Heat capacity studies of magnetic phase transition in sodium-rich NaxCoO₂ (0.73 ≤ x ≤ 0.87) - Baran, A.; Botko, M.; Zorkovská, A.; Kajňaková, M.; Šebek, J.; Šantavá, E.; Peng, J.P.; Lin, C.T.; Feher, A. (Физика низких температур, 2009)
Specific heat measurements in the temperature region from 2 to 50 K in magnetic field up to 10 T, oriented parallel and perpendicularly to the CoO₂ layers were carried out on a series of high-quality single- crystals of NaxCoO₂ (x = 0.73, 0.76, 0.77, 0.78 and 0.87). Surprisingly, sharp lambda type anomaly was observed only for the concentration x = 0.76 at temperature (21.80 ± 0.02) K, for all the remaining doping levels round anomaly in experimental data was visible at temperature ~ 20 K, indicating a smeared magnetic phase transition. While the magnetic field oriented perpendicularly to the CoO₂ layers shifts the temperature of this anomaly to lower values, parallel magnetic field has no influence on it, what indirectly supports the idea of A-type antiferromagnetic ordering in studied systems.